Epidemiological characteristics of patients with carbapenemase-producing NDM Enterobacterales isolates in a high-complexity hospital - Artiles-León, Cristina María; Rodríguez-Restrepo, Sarita; Torres-Jiménez, Ivonne Andrea; de Las Delicias Quintana-Estellés, María; Viedma-Moreno, Esther; Arrazola-Martínez, Pilar; Jaén-Herreros, Felisa; Sanz-Gallardo, Inmaculada; Suárez-García, Esther; Craviotto-Vallejo, Ana; de Miguel-García, Sara (Revista española de quimioterapia, 2025)
Carbapenemase-producing Enterobacteriaceae (CPE) of the New Delhi metallo-β-lactamase (NDM) type are a growing public health concern due to their rapid dissemination, widespread antimicrobial resistance and associated increase in morbidity and mortality. The aim of this study was to describe the epidemiological characteristics of patients with NDM-type CPE (NDM-CPE) isolates. A descriptive study of patients with at least one CPE-NDM isolate between December 1, 2022, and December 31, 2023. Demographic and clinical evolution data were collected from electronic medical records. NDM-CPE were identified in 77 patients, 87% of whom were adults and 75.3% were male. Thirty-two-point five percent were immunosuppressed. A total of 84.4% required hospital admission (60% in ICU) and 66.2% underwent surgery. The median time between admission and the first microbiological isolation of NDM-CPE was 18 days (RIC: 4-32 days). The most frequent microorganism was (92.2%), followed by (4.2%), and (4.2%). A total of 58.4% carried genes coding for NDM and OXA-48 carbapenemases, 40.3% for only NDM, and 1.3% for NDM and VIM. A total of 45.5% were patients with positive colonization samples for NDM-CPE, of whom 31.4% developed infection. Overall mortality at study end was 24.7 %. Early identification of carriers, strengthening epidemiological and molecular surveillance, and prompt implementation of control measures are essential to interrupt transmission chains and protect the most vulnerable patients.